ANALYSIS OF THE INTEGRATED HUMAN CAPITAL SYSTEM (DIGIHC) APPLICATION IN MEASURING EMPLOYEE DISCIPLINE AT PT BANK NEGARA INDONESIA (PERSERO) TBK KCU PER HIGHER EDUCATION BANDUNG - Salsabila, Salsabila; Hendriyani, Chandra; Garnida, Agus (The International Journal of Business Review (The Jobs Review), 2023)
Technological developments in the business world, especially in the field of human resources, can be both opportunities and threats.   To deal with it, human resources must be able to adapt to technological developments and improve their skills.   Technological transformation in human resource management involves collecting, maintaining, and updating employee data as well as activities such as recruitment, selection, training, and Performance management.  Discipline is an important factor in employee assessment, because good discipline can prevent ineffectiveness at work.  Human Resources Information System (HRIS) applications, such as the Integrated Human Capital System (DigiHC), can support effective and efficient management of employee discipline, but challenges remain in the use of these applications, such as filling attendance that is less than optimal. Therefore, this study aims to analyze the use of the DigiHC application in measuring employee discipline at Bank Negara Indonesia (BNI) KCU Perguruan Tinggi Bandung. This research uses a qualitative approach with a descriptive method. Primary data were collected through observation and interviews with related parties, while secondary data came from junals and reports. The results of this research are expected to help BNI in improving employee discipline through the  use of the DigiHC application.